2006
DOI: 10.1192/bjp.bp.105.017269
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in bipolar II disorder

Abstract: Cognitive impairment exists in both subtypes of bipolar disorder, although more so in the bipolar I group. The best predictors of poor psychosocial functioning in bipolar II disorder were subclinical depressive symptoms, early onset of illness and poor performance on a measure related to executive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
189
7
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(233 citation statements)
references
References 38 publications
27
189
7
10
Order By: Relevance
“…Three studies using this test did not find impaired BD II patients (Summers et al 2006 ;Torrent et al 2006 ;Savitz et al 2008). However, Torrent et al (2006) found that BD II patients, as well as BD I patients, showed a trend towards a higher number of perseverative errors compared with HCs, which may also be related to greater impulsivity.…”
Section: Cognitive Flexibilitymentioning
confidence: 97%
See 4 more Smart Citations
“…Three studies using this test did not find impaired BD II patients (Summers et al 2006 ;Torrent et al 2006 ;Savitz et al 2008). However, Torrent et al (2006) found that BD II patients, as well as BD I patients, showed a trend towards a higher number of perseverative errors compared with HCs, which may also be related to greater impulsivity.…”
Section: Cognitive Flexibilitymentioning
confidence: 97%
“…Three studies using this test did not find impaired BD II patients (Summers et al 2006 ;Torrent et al 2006 ;Savitz et al 2008). However, Torrent et al (2006) found that BD II patients, as well as BD I patients, showed a trend towards a higher number of perseverative errors compared with HCs, which may also be related to greater impulsivity. In two studies, cognitive flexibility was evaluated with another measure, the Intra-Dimensional/Extra-Dimensional Set-Shift subtest from CANTAB, with contradictory results ; one of them found that unmedicated BD II depressed subjects demonstrated intact performance (Taylor Tavares et al 2007) and the other found that BD II patients scored significantly lower than BD I patients (Summers et al 2006).…”
Section: Cognitive Flexibilitymentioning
confidence: 97%
See 3 more Smart Citations